8 Expression and Activity of Braf in Cardiomyocytes. (19th January 2014) - Clerk, A; Sugden, P H
Abstract : Rationale: The Raf family (Raf1, ARaf, BRaf) are upstream kinases for the extracellular signal-regulated kinase 1/2 (ERK1/2) cascade which is involved in cell proliferation and survival. Dysregulation of BRaf is associated with cancer, and BRaf inhibitors are in clinical use. In the heart, ERK1/2 signalling is required for cardioprotection and is associated with hypertrophic growth. Although Raf1 and ARaf have been shown to be activated by hypertrophic stimuli in cardiomyocytes, BRaf was not previously detected in cardiac tissue. Methodology: Expression of BRaf protein in adult rat heart and neonatal cardiomyocytes was studied by immunoblotting with N- or C-terminal antibodies. Following immunoprecipitation, activities of Raf1 and BRaf were compared using GST-MKK1 as substrate. Co-immunoprecipitation experiments were performed. Results: BRaf protein was detected in extracts from adult rat hearts or cardiomyocytes as a doublet of 90 kDa (predicted 89 kDa) using antibodies to either the N- or C-terminus. Both bands were immunoprecipitated with any of the antibodies. Activity assays confirmed that Raf1 exhibits low basal activity that is substantially increased by epidermal growth factor (EGF). However, BRaf had substantially greater basal activity that was further increased in response to EGF. As in other cells, BRaf associated with Raf1/ARaf in cardiomyocytes as demonstrated by co-immunoprecipitation. Conclusions: BRaf is expressed in cardiomyocytes and adult hearts at significant levels, it exhibits high basal activity, its activity can be increased by EGF, and it forms complexes with ARaf and Raf1. Thus, the BRaf inhibitors in use for cancer therapy have the potential to affect cardiac function.